A combined approach of differential scanning calorimetry and hot-stage microscopy with image analysis in the investigation of sulfathiazole polymorphism - Abu Bakar, Mohd Rushdi; Nagy, Zoltan K.; Rielly, Chris D. (Springer, 2010)
A combination of differential scanning calorimetry and hot-stage microscopy with image analysis has been used to investigate the polymorphism of sulfathiazole. The use of light intensity profiles obtained from the HSM images, as an alternative way to present results of the HSM analysis, was found to be useful in describing and verifying thermal events. The approach provides a unique insight into the polymorphic transformations and thermal behaviour exhibited by this compound. The results of the experiments show that sulfathiazole tends to crystallise as mixtures of polymorphs, even though the literature methods for producing pure polymorph were followed.